Análisis de la importancia de las estrategias de CRM para la captación, fidelización y retención de clientes de telefonía móvil de Movistar del Perú en el 2020 en Lima Metropolitana - Castro Vargas, Jarinson Ricaldi (2021)
The objective of this thesis is to determine, analyze and generate recommendations on the importance of the CRM strategies applied by Movistar for the acquisition, loyalty, and retention of customers in 2020, which is also supported by literature related to the subject. With a population of 2,606,427 Movistar mobile phone customers in Metropolitan Lima, the study sample was 273 people chosen at random. The data of the present research were collected with the survey technique and its instrument the questionnaires, the latter had 15 questions, later they were processed and analyzed. Finally, the results determined the high degree of importance of the strategies for acquisition and loyalty applied by the company, as well as recommendations regarding retention strategies.